Diversificación de la producción agropecuaria en Nicaragua 1980-2018 - Herrera Aguirrez, José Luis; Miranda Sobalvarro, Xochilt Janire; Vivas Viachica, Elgin Antonio. Asesor (Managua (Nicaragua), 2020)
(Es)
26 ref.
Tesis (Lic. En Agro.)